Democratic and Popular Republic of Algeria : Public Expenditure Review of the Social Sector, Volume 2. Annexes - World Bank (World Bank, Washington, DC, 2015)
This public expenditure review identifies various opportunities to improve efficiency and equity in the social sectors. In terms of efficiency, common issues across sectors include prioritizing public interventions on the basis of their costs and effectiveness, reducing the share of personnel expenditures through a more efficient deployment of human resources, and reviewing financial mechanisms to minimize distortions and induce cost-savings (particularly in the health sector). Reallocating resources towards maintenance services, while encouraging outsourcing practices is another cross-cutting theme. Regarding equity, there is a need in all sectors to improve targeting mechanisms in the allocation of public subsidies. The Government still faces the challenge of reducing gender inequalities, particularly among low-income groups. The message also emerges that the private sector should have a more prominent role both in the financing and provision of social services. Improving institutional capacity, governance, and accountability is also a precondition for higher efficiency and equity. One of the most important recommendations from the review is the need to pursue structural reforms to promote growth, while changing the focus of public expenditure management from driving growth to ensuring stabilization and an efficient supply of public goods. The role of public expenditure in the social sectors should be to guarantee necessary investments in human capital to support growth.